The effect of the addition of various species of mushrooms on the physicochemical and sensory properties of semolina pasta. Issue 16 (20th July 2022) - Szydłowska-Tutaj, Magdalena; Złotek, Urszula; Wójtowicz, Agnieszka; Combrzyński, Maciej
Abstract : Supplementation with dried mushrooms increased the nutritional value of enriched pasta. Abstract : Interest in foods enriched with natural ingredients containing bioactive compounds prompts scientists to undertake research to investigate them. This work aimed to evaluate the chemical composition, physical properties, texture, and sensory properties of semolina pasta enriched with 2.5–10% dried mushroom powder (Lion's Mane (L), Maitake (M), Reishi (R), and Enoki (E)). Supplementation with dried mushrooms increased the nutritional value of all the enriched pasta variants, mainly by increasing the content of ash, protein, and dietary fiber. Fortification with Lion's Mane (10%), Reishi (7.5% and 10%), and Enoki (10%) increased the cooking loss of the pasta. A decrease in L * (lightness) and b * (yellowness) was observed in the enriched pasta, with the exception of the cooked E and L samples. Hardness was increased in the Enoki-supplemented cooked pasta. Only the pasta with 7.5% and 10% Lion's Mane and Reishi mushrooms did not have acceptable sensory attributes. Based on the research, the recommended level of supplementation is 5% for Lion's Mane and Reishi, 7.5% for Enoki, and 10% for Maitake mushrooms.